CROSS-CULTURAL COMMUNICATION ISSUES BETWEEN INDONESIA AND CHINA FROM THE PERSPECTIVE OF THE CHINESE DIASPORA - Waru, Dian Sari Unga; Dan Dan, Liu; Sukma, Sukma; Cahyati, Leni; Faisal, Andi (Bambuti, 2025)
Cross-cultural communication is a process of interaction or communication carried out by two or more cultures which is the transfer of ideas or concepts from one culture to another culture with the intention of bringing the influence of one culture to another culture and vice versa so that they can influence each other, as well as reduce the level of misunderstanding and minimize the occurrence of conflict. This research aims to reveal the forms of issues that occur in everyday life in society related to the issue of cultural differences between Indonesia and China through the perspective of Chinese people living in Indonesia. This research is a qualitative descriptive study using a cross-cultural communication approach with data collected through structured interviews with the Chinese diaspora living in Makassar City. The results of the research are that there are eight (8) differences that are issues of cross-cultural communication between Indonesia and China, namely language barriers, different eating habits, different meal treat habits, different concepts of time, different pace of life, different tipping habits, different toilet habits, and different religious beliefs.